Oral traditional Chinese medicine for mild to moderate cases of COVID-19: a network meta-analysis based on RCTs - Wen Cao; Nannan He; Yannian Luo; Zhiming Zhang (Journal of Infection in Developing Countries)
Introduction: This systemic review examines the effectiveness and safety of combining traditional Chinese medicine with standard therapy in the treatment of mild to moderate cases of coronavirus disease 2019 (COVID-19).